Retained free energy as a driving force for phase transformation during rapid solidification of stainless steel alloys in microgravity. (December 2018) - Matson, Douglas
Abstract Ternary Fe-Cr-Ni stainless steel alloys often exhibit a multi-step transformation known as double recalescence where primary ferrite converts to austenite during rapid solidification processes such as casting and welding. In addition to the volume free energy associated with undercooling between the phases, the free energy driving the transformation comes from two additional sources that are retained within the metastable solid—one from the primary phase undercooling and one from melt shear. A new physical model is proposed based on accumulation of defects, such as dislocations or tilt boundaries, and lattice strain. A dimensionless analysis technique shows that the free energy associated with metastable solidification is conserved and the contribution from melt shear can be predicted based on a modification of the Read-Shockley dislocation energy equation. With these additional terms the incubation time between nucleation events becomes inversely proportional to the total free energy squared for bulk diffusion and cubed for grain boundary diffusion mechanisms. In the case of the ferrous alloys studied, the grain boundary mechanism provides a better fit and when the model is applied the delay time behavior collapses to a single master-curve for the entire alloy family. Alloys: Tracking the evolution from liquid to solid A model that describes the atomic-structure changes in a steel alloy as it rapidly changes from a molten to a solid state is developed by a scientist in the USA. Steel solidifies very quickly after being welded, during which process the atomic structure of the solid alloy can change multiple times. For example, an alloy of iron, chromium and nickel transforms from a ferrite atomic structure to one known as austenite. Classical nucleation theory does not explain this so-called double recalescence. Douglas Matson at Tufts University has developed a novel physical model to describe this microstructural evolution that is based on viewing the transformation as an accumulation of defects. The model predicts the time delay of the transformation, which Matson compares to observed values determined by microgravity experiments.